Red blood cell exchange as an approach for treating a case of severe tacrolimus overexposure. Issue 2 (April 2017) - Spallanzani, Valentina; Bindi, Lucia; Bianco, Irene; Precisi, Arianna; DeSimone, Paolo; Mazzoni, Alessandro; Biancofiore, Gianni
Abstract: Immunosuppressive medication dosing errors are not unfrequent and may present a number of challenges to transplant clinicians. Tacrolimus (TAC) is a widely used immunosuppressant with a narrow therapeutic index and potential severe side effects, including neurotoxicity and kidney injury. We herein report a case of 60-year-old woman who underwent deceased-donor liver transplantation at our center and due to inadvertent TAC overexposure was admitted to the Intensive Care Unit because of severe neurologic impairment, kidney injury and arterial hypotension. This case was challenging because TAC is largely bound to erythrocytes, has a high molecular weight, is highly lipophilic, has a high distribution volume and cannot be removed by hemodialysis or plasmapheresis. Based on these considerations, we decided to replace TAC-saturated erythrocytes with blood-bank red cells with the aim to accelerate its clearance. The treatment was effective in decreasing TAC whole blood trough levels within the therapeutic ranges with a significant improvement of the patient's clinical status. Red-blood cell exchange is a potentially safe and effective means of managing severe and symptomatic TAC toxicity.